Direct Operation of Solid Oxide Fuel Cells on Low-Concentration Oxygen-Bearing Coal-Bed Methane with High Stability - Jiao, Yong; Wang, L.; Zhang, L.; An, Wenting; Wang, Wei; Zhou, W.; Tade, Moses; Shao, Zongping; Bai, J.; Li, S. (American Chemical Society, 2018)
This paper studies the electrochemical feasibility of the direct conversion of low-concentration, oxygen-bearing coal-bed methane (CBM, 30 vol % CH4) to electricity via solid oxide fuel cells (SOFCs). A fuel cell with the LiLaNi–Al2O3/Cu catalyst layer was developed, and a maximum power output of ∼1068 mW cm–2 was achieved at 850 °C using 30 vol % CBM fuel, which is only modestly lower than that from a cell based on hydrogen fuel. The stability test showed that the cell operation was quite stable during the 120-h test period, which is ∼40-fold longer than that of the cell without catalyst layer. The partial oxidation of methane (POM) occurring in the anode may play an important role when using 30 vol % CBM fuel, which not only supplies highly active gaseous fuels (H2 and CO) but also suppresses the carbon deposition on the anode. By modifying the anode with a LiLaNi–Al2O3/Cu catalyst layer, the POM of 30 vol % CBM was further promoted and the carbon deposition over the anode was mitigated more efficiently. Therefore, the strategy of direct conversion of low-concentration, oxygen-bearing CBM via the SOFCs with an anode catalyst layer may pave an alternative way to utilize this abundant resource efficiently and cleanly.